POTENSI EKSTRAK METANOL DARI DAUN PEPAYA (Carica papaya L) SEBAGAI BIOLARVASIDA PADA LARVA NYAMUK Aedes aegypti L - Nuri Andri Susanti, ; Sri Hidayati Syarief, (Matematika dan Sains, 2010)
The aims of this research were to know the enfluence of concentration of Carica papayas methanol extract to lethality of Aedes aegyptis larvas and to determine the biolarvaside activity of Carica papayas methanol extract against Aedes aegyptis larvas. In this research, extraction conducted using maceration method and biolarvaside activity (LC-50) was analyzed by probit analysis. The results of research showed that concentration of Carica papayas methanol extract enfluenced the lethality of Aedes aegypti larvas with LC-50 of 1409,61 ppm.